Autophagy Regulation Influences β-Amyloid Toxicity in Transgenic Caenorhabditis elegans - Lin, Hongru; Gao, Yehui; Zhang, Chen; Ma, Botian; Wu, Mengchen; Cui, Xianghuan; Wang, Hongbing (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a progressive, neurodegenerative disease characterized by the accumulation of amyloid-beta (Aβ) proteins in the form of plaques that cause a proteostasis imbalance in the brain. Several studies have identified autophagy deficits in both AD patients and AD animal models. Here, we used transgenic Caenorhabditis elegans to study the relationship between autophagy flux and Aβ. We labeled autophagosomes with an advanced fluorescence reporter system, and used this to observe that human Aβ expression caused autophagosome accumulation in C. elegans muscle. The autophagy-related drugs chloroquine and 3-MA were employed to investigate the relationship between changes in autophagic flux and the toxicity of Aβ expression. We found that reducing autophagosome accumulation delayed Aβ-induced paralysis in the CL4176 strain of C. elegans, and alleviated Aβ-induced toxicity, thus having a neuroprotective effect. Finally, we used RNA-sequencing and proteomics to identify genes whose expression was affected by Aβ aggregation in C. elegans. We identified a series of enriched autophagy-related signal pathways, suggesting that autophagosome accumulation impairs Aβ protein homeostasis in nematodes. Thus, maintaining normal autophagy levels appears to be important in repairing the protein homeostasis imbalance caused by Aβ expression.